GROWTH ANALYSIS IN RABBIT USING GOMPERTZ NON-LINEAR MODEL - A. Setiaji; S. Sutopo; E. Kurnianto (Diponegoro University, 2013)
An experiment was conducted to compare the growth curve of rabbit. Three breeds of rabbit,namely Indonesian Local Rabbit (IL), Flamish Giant (FG) and Rex (R) were used in the study.Individual body weights of each breed was measured from birth to 63 days of age with 3-days interval.Those periodical data were separated into different sex, be then it was averaged to analysis growthpattern. Growth curve parameters were estimated to fit growth data. There was no difference in bodyweight between sexs within breed. Indonesian local rabbit had the lowest body weight. The resultsshowed that growth curve paramaters among three breeds were significantly different (P<0.05) for bothsexes. FG had the highest value of asymptotic mature weight, followed by R and IL. In conclusion,Gompertz model was excellent fit for the growth data in rabbit with a high coefficient determination (R2= 0.999).